Pre‐operative anaemia. (January 2015) - Clevenger, B.; Richards, T.
Summary: Pre‐operative anaemia is a relatively common finding, affecting a third of patients undergoing elective surgery. Traditionally associated with chronic disease, management has historically focused on the use of blood transfusion as a solution for anaemia in the peri‐operative period. Data from large series now suggest that anaemia is an independent risk associated with poor outcome in both cardiac and non‐cardiac surgery. Furthermore, blood transfusion does not appear to ameliorate this risk, and in fact may increase the risk of postoperative complications and hospital length of stay. Consequently, there is a need to identify, diagnose and manage pre‐operative anaemia to reduce surgical risk. Discoveries in the pathways of iron metabolism have found that chronic disease can cause a state of functional iron deficiency leading to anaemia. The key iron regulatory protein hepcidin, activated in response to inflammation, inhibits absorption of iron from the gastrointestinal tract and further reduces bioavailability of iron stores for red cell production. Consequently, although iron stores (predominantly ferritin) may be normal, the transport of iron either from the gastrointestinal tract or iron stores to the bone marrow is inhibited, leading to a state of 'functional' iron deficiency and subsequent anaemia. Since absorption from the gastrointestinal tract is blocked, increasing oral iron intake is ineffective, and studies are now looking at the role of intravenous iron to treat anaemia in the surgical setting. In this article, we review the incidence and impact of anaemia on the pre‐operative patient. We explain how anaemia may be caused by functional iron deficiency, and how iron deficiency anaemia may be diagnosed and treated.